Elements of group dynamics that influence learning in small groups in undergraduate students: A scoping review. (April 2020) - Dionne Merlin, Marjolaine; Lavoie, Stéphan; Gallagher, Frances
Abstract: Background: Learning in small groups is a frequent activity in undergraduate programs to enrich learning, as well as in nursing programs during clinical experiences. Being in a small group adds elements of group dynamics that influence learning. Research into the influence of these elements on learning in small groups is not clear in the literature. This makes it challenging for educators to promote the optimal environment for learning. Objective: To explore the literature on elements of group dynamics that influence learning in small groups among undergraduate students. Design and data sources: A scoping review was performed, inspired by the five-stage approach of Arksey and O'Malley and the methodology outlined by the Joanna Briggs Institute. Various databases were used including CINAHL, ERIC, psycINFO, PubMed and Science Direct. Review method: Our research question was: What are the elements of group dynamics that influence learning in small groups among undergraduate students? At least two authors analyzed the relevant studies and data were extracted to describe the elements of group dynamics that influence learning in small groups among undergraduate students. Results: Thirty papers were included in our review. Five elements emerged: engagement, openness, support, quality of communication and style of dominant behavior. Conclusions: The results suggested the utilization of these elements in establishing a group dynamic favorable for learning in small groups. Since little research has been done into group dynamics in nursing education, it was useful to explore this concept in other disciplines. Further research is needed with a focus on clinical education for nursing students.